Adherence to and Forgiveness of 3TC/DTG in a Real-World Cohort. (June 2022) - Maggiolo, Franco; Valenti, Daniela; Teocchi, Rodolfo; Comi, Laura; Filippo, Elisa Di; Rizzi, Marco
Background: adherence and forgiveness are key factors for virologic success. We evaluated them for 3TC/DTG.Methods: pharmacy refills were used to calculate the proportion of days covered (PDC). Forgiveness was calculated as the achieved rate of HIV-RNA threshold by a given level of imperfect adherence.Results: 240 PLWH were included. The median follow-up was 819 days (IQR 450-1459) for a total of 681 person/years of follow-up. Adherence was very high with a median of 99% (IQR 95%-100%). Consequently, the virologic response was sustained with 83.8% of PLWH never exceeding a HIV RNA of 50 copies/ml and 95.8% of subjects with a steadily HIV-RNA < 200 copies/ml. A PDC lower than 80% was associated with a negative outcome irrespective of the HIV-RNA threshold considered.Conclusions: The extensive virologic efficacy of 3TC/DTG demonstrated both in clinical trials and real-world experiences seems to rely more on its friendliness than on its forgiveness.